Revision techniques: Interleaving and spacinga. (1st April 2019) - Webb, Helen
Abstract : 'Spacing' refers to revision throughout the course of study, while 'interleaving' means switching between ideas while you learn. Both techniques can help boost students' long-term memories and retrieval of key information. Helen Webb explains